2016
DOI: 10.30699/10.30699/jidai.28.1.14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Microleakage of Class V Composite Restorations in Use of Three Adhesive Systems

Abstract: Background and Aim: Microleakage is a drawback of composite restorations and it is more noticeable in dentinal walls. Despite advances in dentin bonding agents, no adhesive can completely eliminate microleakage and provide a hermetic seal. This study aimed to compare microleakage of three resin bonding agents namely a universal adhesive, two-step self-etch system and two-step total-etch system. Materials and Methods: This in vitro, experimental study was conducted on 68 human molars. Class V cavities were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Etching with phosphoric acid or with acidic primers changes the surface morphology and chemical composition.Moreover, the tubules orientation can change the hybrid layer formation [32]. The results of some other studies also showed that the enamel marginal leakage was similar when universal bonding systems were used with the etch and rinse or self-etch strategy which led to the conclusion that an additional step of selective enamel etching is not necessary [16]. The same study showed similar bonding to dentin for the universal bonding systems applied in both strategies.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Etching with phosphoric acid or with acidic primers changes the surface morphology and chemical composition.Moreover, the tubules orientation can change the hybrid layer formation [32]. The results of some other studies also showed that the enamel marginal leakage was similar when universal bonding systems were used with the etch and rinse or self-etch strategy which led to the conclusion that an additional step of selective enamel etching is not necessary [16]. The same study showed similar bonding to dentin for the universal bonding systems applied in both strategies.…”
Section: Discussionmentioning
confidence: 73%
“…Studies have shown a similar bonding performance of universal adhesives when comparing to the selfetch adhesives and etch and rinse adhesives [16].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on previous studies, this bonding agent has a favorable bond strength irrespective of the etching techniques. It prevents post-operative hypersensitivity due to proper penetration and wettability and low viscosity [24,25].…”
Section: Dye Penetrationmentioning
confidence: 99%
“…It was previously shown that Scotch Bond universal adhesive has a performance similar to that of Adper Single Bond ® 2 and Clearfil SE ® Bond; however, its microleakage at the gingival margins of Cl V cavities was higher compared to occlusal margins [25]. Also, another study revealed that the microleakage of Cl V composite resin restorations with the use of self-etch universal adhesives in the self-etch mode at the occlusal margins was less than that with the total-etch mode, and in both modes, the microleakage at gingival margins was higher than that at the occlusal margins [27].…”
Section: Dye Penetrationmentioning
confidence: 99%